Respuesta :
Answer:
Shift 2 unit left
Flip the graph about y-axis
Stretch horizontally by factor 2
Shift vertically up by 2 units
Step-by-step explanation:
Given:
Parent function: [tex]f(x)=\log x[/tex]
Transformation function: [tex]f(x)=\log(-2x-4)+2[/tex]
Take -2 common from transform function f(x)
[tex]f(x)=\log[-2(x+2)]+2[/tex]
Now we see the step-by-step translation
[tex]f(x)=\log x[/tex]
Shift 2 unit left ( x → x+2 )
[tex]f(x)=\log(x+2)[/tex]
Flip the graph about y-axis ( (x+2) → - (x+2) )
[tex]f(x)=\log[-(x+2)][/tex]
Stretch horizontally by factor 2 [ -x(x+2) → -2(x+2) ]
[tex]f(x)=\log[-2(x+2)][/tex]
Shift vertically up by 2 units [ f(x) → f(x) + 2 ]
[tex]f(x)=\log[-2(x+2)]+2[/tex]
Simplify the function:
[tex]f(x)=\log(-2x-4)+2[/tex]
Hence, Using four step of transformation to get new function [tex]f(x)=\log(-2x-4)+2[/tex]
Answer and explanation:
To find : Describe the transformation(s) that take place on the parent function, [tex]f(x) =\log(x)[/tex], to achieve the graph of [tex]g(x) = \log(-2x-4) +2[/tex]
Solution :
Parent function: [tex]f(x) =\log(x)[/tex]
Transformation function: [tex]g(x) = \log(-2x-4) +2[/tex]
Re-write the transformed function by taking -2 common,
[tex]g(x) =\log(-2(x+2))+2[/tex]
Step 1 - Shift 2 unit left i.e, f(x)→f(x+b) shifting left by b unit in parent function,
[tex]f(x)=\log(x+2)[/tex]
Step 2 - Flip the graph about y-axis i.e, f(x)→ -f(x)
[tex]f(x)=\log[-(x+2)][/tex]
Step 3 - Stretch horizontally by factor 2 i.e, f(x)→f(bx) stretch horizontally by b unit
[tex]f(x)=\log[-2(x+2)][/tex]
Step 4 - Shift vertically up by 2 units i.e, f(x)→f(x)+b shifting vertically by b unit
[tex]f(x) =\log(-2(x+2))+2=g(x)[/tex]
In four steps the transformation is done.